Education stategies in european context: a survey of teaching learning approaches, tools and assessment among physiotherapy teachers - Alves Lopes, António (2022)
Background: The context of education in the health professions has been influenced by the same tendencies of development of knowledge and technology that society faces. It is therefore important that educational institutions are capable of promoting an evolutionary profile of professionals that is adapted to the needs of the future society. Purpose: One of the aims of the European Network of Physioth erapy in Higher Education (ENPHE) is to bring together and enhance collaboration between european institutes and physiotherapy educational institutions in the european region in order to encourage and support standards of high quality education in physiotherapy in accordance with the recommendations of the World Confederation for Physical Therapy (WCPT and ER-WCPT). Methods: In the context of the ENPHE group “Facilitation of Learning” and based on the literature, an online questionnaire was constructed regarding teaching approaches. After a pilot study within 5 institutions, the final version of the survey was disseminated during the ENPHE 2018 seminar. Results: We h ad 143 survey responses from 19 countrys, most of the respondents were fulltime lecturers (54%) at Bachelor´s level (89%). The responses indicated that the most commonly used Learning. Approaches included, Problem Solving (86%) and Content Focus activities (83%) using mainly lectures (78%) and practical training in class (83%) and the most popular tools used were aimed to facilitate retrieving, recalling or recognising knowledge (97%), using written (86%) and/or practical examination (77%) as assessment strategies. Conclusion(s): The results still reflect a classic approach to teaching and learning as shown by the selection of approaches, tools and assessment strategies. Implications: The results have provided some insight and also could guide the ENPHE in devising strategies to facilitate the use of more student inclusive and active learning strategies in Physiotherapy education.